Leadership mindset [ innovation and learning in the transformation of schools - Kaser, Linda; Halbert, Judy , 1949- (Leading school transformation, 2009)
Why are some leaders able to raise student achievement in schools in the most challenging circumstances whilst other leaders struggle to simply maintain the status quo? This title argues that there